A review of Suicide Behavior Among Arab Adolescents. (2005) - Morad Morad, Mohammed Mohammed; Merrick Merrick, Efrat Efrat; Schwarz Schwarz, Amir Amir; Merrick Merrick, Joav Joav
Abstract : Islam prohibits the taking of one's life, because this way you will interfere with the work of G-d (Allah), which is clear from several places in the Quran. Concerning individual suicide or suicide attempts in various Arab countries the literature is sparse and the incidence low. In this paper we present a review of research from Israel showing that suicide epidemiology among the Arab population of children and adolescents display a low incidence, but an increase has been observed over the past decade, but still much lower than the Jewish population. We believe that there is a need for the development of prevention and intervention strategies in order to keep this incidence low.